“I USE MULTIPLE-CHOICE QUESTION IN MOST ASSESSMENT I PREPARED”: EFL TEACHERS’ VOICE ON SUMMATIVE ASSESSMENT - Nadita Antania Rachmat; Puput Arfiandhani (ETERNAL (English, Teaching, Learning and Research Journal), 2019)
The study aimed at investigating Senior High School English teachers’ views on the drawbacks and the strengths of the employement of Multicple Choice Question as a summative assessment. Rooting within qualitative research paradigm, the current study employed descriptive qualitative design. The data were collected through in-depth interview with three experienced EFL teachers of a prominent state senior high school in Banjar, West Java. The results of the interview indicated that there are three strengths in using Multiple-Choice Question (MCQ) as a summative assessment. These strengths included teachers’ view that MCQ could result in quick and easy scoring, facilitate the assessment of varied language skills and encourage the students to answer the question carefully. Additionally, there were three drwabacks in using MCQ as a summative assessment such as teachers’ view that MCQ could only facilitate on low order of critical thinking, have low positive washback and require a lot of time in its designing phase. Interestingly, two out of three participants thought that MCQ has been a mandatory type of summative assessment suggested by the government. However, in fact, there has been no government policy which recommend certain type of summative assessment. Therefore, looking at the strengths and drawbacks of the use of MCQ could help to be better informed before deciding to use MCQ as a summative assessment.